IMPLEMENTATION OF RESTORATIVE JUSTICE IN RESOLVING FAMILY CONFLICTS FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW - Tedy Subrata; Hikmatullah Hikmatullah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the urgency and mechanisms of implementing Restorative Justice in resolving family conflicts from the perspective of Islamic Family Law. Amid the high rates of divorce and domestic violence, formal litigation approaches often fail to repair fractured relationships among family members. This research employed a qualitative method with a normative juridical approach. Data were collected through literature studies of Islamic legal texts, Indonesian statutory regulations, and related literature on Restorative Justice. The findings indicate that the concept of Restorative Justice has strong relevance to the principle of Ishlah (reconciliation) in Islamic Family Law. Unlike the retributive approach, which focuses on punishment, Restorative Justice prioritizes relationship recovery, forgiveness, and collective welfare. In practice, instruments such as mediation in Religious Courts and the role of Hakam (peace mediators) represent clear manifestations of these restorative values. The study concludes that integrating Restorative Justice into the family law system is not only effective in reducing divorce rates but also capable of preserving the psychological well-being of family members, especially children. The academic contribution of this study lies in providing a theoretical foundation for the development of positive law in Indonesia to become more accommodative toward non-litigation dispute resolution based on religious values and local wisdom. The researcher recommends strengthening technical mediation regulations so that they do not merely become procedural formalities in court.